Penerapan sistem intercropping dalam pengelolaan hama tanaman jagung (Zea mays L.) - Anita; Muhanniah; ⁠Nining Triani Thamrin (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2025)
Maize production in tropical regions is frequently threatened by insect pests, leading to significant yield losses. Environmentally friendly strategies such as intercropping offer potential solutions for pest suppression while enhancing crop productivity. This study aimed to evaluate the effectiveness of different intercropping combinations in improving maize production by reducing pest pressure. The research was conducted using a Randomized Block Design (RBD) with five treatments: monoculture maize, and maize intercropped with groundnut, citronella, Zinnia refugia, and chili, each replicated three times. Observed variables included yield components such as the number of kernel rows per cob, kernels per row, weight of 100 kernels, and yield per unit area. Results showed that maize intercropped with Zinnia refugia produced the highest performance in most yield components, significantly increasing row number per cob, kernels per row, and total yield compared to monoculture. Meanwhile, citronella intercropping resulted in the highest 100-kernel weight. In contrast, intercropping with chili resulted in the lowest yield, possibly due to resource competition or allelopathic effects. The findings suggest that specific intercropping patterns, particularly those involving refugia or repellent plants, can enhance maize productivity and serve as effective pest management strategies. Further research is recommended to validate these findings under diverse agroecological conditions.